Ideologi Agama dalam Praktik Dominasi antara LDII Versus Non-LDII di Jombang - Limas Dodi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2018)
This article reviews the religious ideology in the practice of domination of Lembaga Dakwah Islam Indonesia (LDII) over non-LDII communities in Gading Mangu Perak Jombang East Java. Using a phenomenological approach, this article concludes that as an ideology, religion functions to legitimize an action. Belief in religion as an ideology is very susceptible to the interests of domination. LDII Gading Mangu allowed the society to exchange knowledge through both pengajian (religious preaching) at the GAMA Islamic Boarding School and to attend formal schools at Budi Utomo Foundation owned by LDII. It has been evident that although there are two large educational institutions under the auspices of the Nahdlatul Ulama in the same area, the Budi Utomo Foundation has superior quality and quantity. Therefore, it attracts the common people or non-LDII members to send their children to Budi Utomo School. Within the economic field, LDII Gading Mangu set up its dominance by establishing a Joint Business (UB), which vends various goods and services, not only for its members but also for the non-LDII people.